2019
DOI: 10.3390/children6040052
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation and Hemodynamics during Chest Compressions in a Lamb Model of Perinatal Asphyxia Induced Cardiac Arrest

Abstract: The current guidelines recommend the use of 100% O2 during resuscitation of a neonate requiring chest compressions (CC). Studies comparing 21% and 100% O2 during CC were conducted in postnatal models and have not shown a difference in incidence or timing of return of spontaneous circulation (ROSC). The objective of this study is to evaluate systemic oxygenation and oxygen delivery to the brain during CC in an ovine model of perinatal asphyxial arrest induced by umbilical cord occlusion. Pulseless cardiac arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Our findings of a rapid, transient increase in carotid artery flow and oxygen delivery following ROSC are consistent with previous lamb studies in the transitional period 14 17 . Studies in asphyxiated lambs and piglets receiving 100% FiO 2 found higher cerebral tissue levels of oxygen than those in lambs that received 21% FiO 2 14 , 32 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings of a rapid, transient increase in carotid artery flow and oxygen delivery following ROSC are consistent with previous lamb studies in the transitional period 14 17 . Studies in asphyxiated lambs and piglets receiving 100% FiO 2 found higher cerebral tissue levels of oxygen than those in lambs that received 21% FiO 2 14 , 32 .…”
Section: Discussionsupporting
confidence: 93%
“…While high levels of alveolar partial pressure of oxygen may be achieved during CPR in 100% FiO 2 , pulmonary flow is low despite chest compressions, so blood oxygen content is likely to be low 17 . Similarly, antegrade carotid flow is limited to the compression phase and oxygen delivery to the brain is likely to remain low until ROSC 17 . Maximising blood oxygen content during the low-output state that characterises the need for CPR may shorten the duration of severe cerebral hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This transient recovery is followed by a secondary deterioration involving a failure of oxidative metabolism (secondary phase) [5][6][7], which is associated with excitotoxic edema, seizures, cerebral hyperperfusion, and ultimately, brain cell death [8]. The term HIE is preferred over perinatal asphyxia [9], and clinical markers, such as fetal heart rate variability [10], blood gases from umbilical cord or Apgar scores, among others, are required to determine the risk of developing brain injury [11]. These clinical markers are currently being used in the clinical setting with approximately 80% sensitivity and specificity [12].…”
Section: Introductionmentioning
confidence: 99%